Emotional Quotient Clinical Nurses Analysis During Covid-19 Pandemic At The Palang Biru Kutoarjo Hospital - Retno Budiati; Vivi Retno Intening; I Wayan Sudarta; Yullya Permina (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Background: Nurses are at forefront of handling the Covid-19 pandemic. Fatigue and anxiety due to the risk of contracting Covid-19 increase the work stress of nurses which has an impact on the emotional instability of nurses, resulting in an increase in patient complaints. The increase in patient complaints also occurred at the Palang Biru Hospital during Covid-19 pandemic specially regarding nursing services. That complaints consist of nursing communication and personal sensitivity. Objective: This study aims to determine the relationship between the level of clinical nurses and an emotional quotient of nurses at the Palang Biru Kutoarjo Hospital during the Covid-19 Pandemic. Methods: This study used a correlative method with a cross sectional approach. The sample obtained was 70 nurses by purposive sampling technique. The data were collected by questionnaire. Data analysis was proceed applying Chi Square with 95% confidence level. Result: Most of the respondents were at the clinical nurse level III as many as 27 respondents (38.6%). The major of emotional quotient are in the low category, there are 46 respondents (65.7%) from 70 respondents. The results of Chi Square test obtained P value = 0.001 where the P value < 0.05 which means there is a positive correlation. Conclusion: There is a close relationship between the level of clinical nurses and the emotional quotient of nurses during the Covid-19 pandemic at the Palang Biru Kutoarjo Hospital.